Navigating Health and Community Services After Traumatic Brain Injury: Experiences and Priorities of Black TBI Survivors - Oluwadamilola Adesina; Lilcelia Williams; Mario Millsap; Daniel Cheluget; Noemi Rojas Serrano; Jessica Kersey (Journal of Head Trauma Rehabilitation, 2026)
Objective: Traumatic brain injury (TBI) disproportionately affects Black Americans, who often experience poorer functional outcomes than their White counterparts. These disparities are exacerbated by limited access to rehabilitation and community-based services. Although current literature has examined the specific barriers Black TBI survivors face in accessing these services, few studies have identified alternative sources of support when services are unavailable. This study aimed to identify the barriers to care, existing support systems, and the services most highly prioritized by Black TBI survivors. Setting: Academic research laboratory. Design: We conducted surveys and qualitative interviews with Black TBI survivors (n = 8) and their family caregivers (n = 6). Survey data were analyzed using descriptive statistics, and qualitative data were analyzed with reflexive thematic analysis. The analysis was guided by the Community Cultural Wealth model, which describes 6 forms of capital that marginalized communities use to navigate systemic barriers. Results: Survey findings revealed that most participants (62.5%) were unaware of community-based brain injury programs. Barriers to accessing services included lack of awareness (75.0%), financial considerations (37.5%), and difficulty understanding eligibility (37.5%). We identified 3 qualitative themes: (1) participants were rich in familial and social capital, relying heavily on family and community networks for support; (2) health care and social service systems undermined navigational capital through long wait times, appointment cancellations, inadequate follow-up, and restrictive insurance policies; and (3) participants prioritized holistic, personalized care and opportunities for peer connection with others who had similar experiences. Conclusions: Findings highlight the need for culturally informed interventions, enhanced navigational support, family-centered services, peer support programs, and policy reforms to improve recovery outcomes for Black TBI survivors.